Low‐Resistance Porous Nanocellular MnSe Electrodes for High‐Performance All‐Solid‐State Battery‐Supercapacitor Hybrid Devices. Issue 7 (11th June 2018) - Tang, Haichao; Yuan, Yuliang; Meng, Lu; Wang, Weicheng; Lu, Jianguo; Zeng, Yujia; Huang, Tieqi; Gao, Chao
Abstract: Searching for materials with improved electrochemical behaviors is an important topic in portable energy storage devices. In this work a simple one‐step solvothermal process is developed to rationally synthesize nanocellular α‐MnSe and its applications in energy storage devices are studied. The MnSe faradic electrode shows a low internal resistance (0.37 Ω), high capacity (84.7 mAh g −1 at 10 mV s −1 ), good rate capability, and long cycle life. All‐solid‐state battery‐supercapacitor hybrid (BSH) devices are assembled using binder‐free nanocellular MnSe as the positive electrode and active carbon (AC) as the negative electrode. The MnSe//AC all‐solid‐state devices exhibit large energy and power densities (39.6 µWh cm −2 at 0.96 mW cm −2 ), extremely low internal resistance (only 1.34 Ω), fast charge process, outstanding cycle stability (119.79% retention after 8000 cycles), and flexibility with rather low bending loss. The wrist strap product by connecting three MnSe//AC all‐solid‐state devices in series can readily drive a green light‐emitting diode for 3 min after 5 s of charging process. This work demonstrates that MnSe is an ideal low‐resistance candidate of electrode materials for all‐solid‐state BSH devices, which is expected to facilitate the development in the portable and wearable energy storage. Abstract : A simple solvothermal process is developed to rationally synthesize nanocellular α‐MnSe . The fabricated MnSe//AC all‐solid‐state battery‐supercapacitor hybrid devices exhibit rather low resistance, large energy and power densities, and excellent cycle stability, with a derived wrist strap product to readily drive a green light‐emitting diode (LED). The MnSe is an ideal electrode material for all‐solid‐state energy storage especially in portable and wearable devices.